Supporting National Immunization Technical Advisory Groups in the WHO European Region in developing national COVID-19 vaccination recommendations through online communication platform - Mosina, Liudmila; Külper-Schiek, Wiebe; Jacques-Carroll, Lisa; Earnshaw, Andrew; Harder, Thomas; Martinón-Torres, Federico; Wilder-Smith, Annelies; Wichmann, Ole; Datta, Siddhartha Sankar (Vaccine, 2021)
National Immunization Technical Advisory Groups are groups of multi-disciplinary experts that provide scientific advice to policy makers to enable them to make informed immunization policy and programme decisions. NITAGs faced challengesusing their routine approach to develop recommendations for COVID-19 vaccines during the pandemic. In response, the WHORegional Office for Europe (Regional Office), with the support of theRobert Koch Institute, developedan innovative approach of a series of webinars, provision of materials, and remote technical assistance to address these challenges. Polls conducted during webinars were used to tailor future webinars and evaluate the effectiveness of these interventions. According to poll results, 76% of participants found the webinars and resources shared very useful in their work on COVID-19 vaccination.The Regional Office plans to build further upon the scope of online communication and establish a regional online platform for NITAGs to further support NITAGs and build capacity.
Gesehen am 30.12.2021